The effects of a 12-week combined aerobic and resistance training program on HRV in individuals with T2DM and examined its associations with glycemic, lipid, and inflammatory (C-reactive protein, CRP) markers - Dr. Kavindra Kumar, Dr. Ashutosh Jain,Dr. Dhiraj Mahaseth, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Aerobic and resistance exercise have been shown to enhance heart rate variability (HRV), yet themagnitude, sustainability, and underlying metabolic and inflammatory mechanisms of these effects remain unclear.This is particularly